Goldilocks and the three bears - McClintock, Barbara 1955- (Scholastic, 2004)
A little girl walking in the woods finds the house of the three bears and helps herself to their belongings. Back cover has recipe for Mama Bear's porridge cookies
Keywords: Bears / Juvenile fiction; Girls / Juvenile fiction